2015
DOI: 10.1134/s1063772915070045
|View full text |Cite
|
Sign up to set email alerts
|

Solar-type activity: Epochs of cycle formation

Abstract: The diagram of indices of coronal and chromospheric activity allowed us to reveal stars where solar-type activity appears and regular cycles are forming. Using new consideration of a relation between coronal activity and the rotation rate, together with new data on the ages of open clusters, we estimate the age of the young Sun corresponding to the epoch of formation of its cycle. The properties of the activity of this young Sun, with an age slightly older than one billion years, are briefly discussed. An anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The 1.6-yr activity cycle of ι Hor was first identified by Metcalfe et al (2010) in chromospheric emission and, using additional Ca H & K data, Flores et al (2017) recently suggested the presence of a secondary ∼4.5-yr periodicity. As very young stars show erratic and non-cyclic activity (see Baliunas et al 1995, Saar & Brandenburg 1999, Katsova et al 2015, Oláh et al 2016, the magnetic and activity cycles of ι Hor could be representative of the onset of cycles during the life of a Sun-like star and provide critical information to understand the generation and evolution of magnetism in late-type stars.…”
mentioning
confidence: 99%
“…The 1.6-yr activity cycle of ι Hor was first identified by Metcalfe et al (2010) in chromospheric emission and, using additional Ca H & K data, Flores et al (2017) recently suggested the presence of a secondary ∼4.5-yr periodicity. As very young stars show erratic and non-cyclic activity (see Baliunas et al 1995, Saar & Brandenburg 1999, Katsova et al 2015, Oláh et al 2016, the magnetic and activity cycles of ι Hor could be representative of the onset of cycles during the life of a Sun-like star and provide critical information to understand the generation and evolution of magnetism in late-type stars.…”
mentioning
confidence: 99%
“…We assume that regular cycles form within this type of activity. In more detail the evolution of the activity is considered by Katsova & Livshits (2011) and Katsova et al (2015). The stars in the second group obey Skumanich law v ∼ √ t, where v is the rotation velocity, t is the age of the star.…”
Section: Introductionmentioning
confidence: 99%
“…For a saturated mode of activity, stellar dynamo is expected to enhance a quasi-stationary magnetic field with chaotic variations, yet without a pronounced cycle (Baliunas et al 1996). A regular cycle begins when the saturated regime of activity changes to the solar-type one, in which the activity level depends on the rotation period (Katsova et al 2015). Nizamov et al (2017) showed that the activity of late spectral-type K stars transitions to exhibiting regular cycles when its rotation period is equal to 3 days.…”
Section: Discussionmentioning
confidence: 99%